Trying Leviathan: The Nineteenth-Century New York Court Case that Put the Whale and Challenged the Order of Nature - Anderson, E. N. (Ethnobiology Letters, 2010)
Review of Trying Leviathan: The Nineteenth-Century New York Court Case that Put the Whale and Challenged the Order of Nature. D. Graham Burnett. 2007. Princeton University Press. Pp. 304 color plates, halftones, bibliography, index. 29.95 (cloth). ISBN 9780691129501.